Preliminary Design of Fluxgate Magnetometer Using Double Pick-Up Coil For Tracking Position in Three Dimensional - PRAGINDA (NIM 20205003), WANDY
It has been developed a magnetic sensor which capable in determining the position of objects in three dimensional based on the change of external magnetic field using Fluxgate Magnetometer (FGM). The construction of developed FGM consists of two cores. In each core, there are two excitation coils and two pick-up coils. This kind of FGM is working based on the second harmonization principle. Excitation coil functions as an internal magnetic field generator and the pick-up coil functions as a receiver of the change of magnetic field. The magnetic field that is generated by the excitation coil will be covered by the pick-up coil and part of the field will be scattered out. The existence of external magnetic field will affect on the intensity of the field which is captured by the pick-up coil. The external magnetic field comes from a magnet which is become a system with the object which the position will be determined by the sensor. The longer the distance between the object and the sensor, will decrease the signal of the magnetic field to the sensor, also happen in the contrary. The external field will be superposed with the excitation magnetic field. The yield will be received by the pick-up coil and changed into induced voltage. Based on the second harmonization principle, intensity of the external magnetic field is proportional with the distance of the object's position. Three dimensional FGM has three sensor that perpendicular to each other which measure the components of the external magnetic field. This is usefull for the detection of magnetic field based on direction parameter of axes x, y, and z, where it will be used as a supplement parameter for determining of the object's position. This modification of FGM is capable in detecting the distance changing between the sensor and the external filed source. This changing is used as the basis of the determination of the object's position using the distance changing as the amplitude on a certain object's position. Based on the analysis of the data was received by the sensor's sensitivity sensor x, sensor y and sensor z that 156.3742 mV/uT, 137.9702 mV/uT,and 144.5448 mV/uT respectively. The sensors can detect magnetic field in range 6,5-20 cm. The maximum absolute error that was received from the polynomial function approached above was -0.39 cm, 0,28 cm dan -0.45 cm and the level of the maximum relative error of the sensor system in this approach was 2,9%, 2,09% dan 3,38%, respectively.